Debating the drug war : race, politics, and the media - Rosino, Michael L. (New York, NY : Routledge, 2021)
Since President Nixon coined the phrase, the "War on Drugs" has presented an important change in how people view and discuss criminal justice practices and drug laws. The term evokes images of militarization, punishment, and violence, as well as combat and the potential for victory. It is no surprise then that questions such as whether the "War on Drugs" has "failed" or "can be won" have animated mass media and public debate for the past 40 years.Through analysis of 30 years of newspaper content, Debating the Drug War examines the social and cultural contours of this heated debate and explores how proponents and critics of the controversial social issues of drug policy and incarceration frame their arguments in mass media. Additionally, it looks at the contemporary public debate on the "War on Drugs" through an analysis of readers' comments drawn from the comments sections of online news articles.Through a discussion of the findings and their implications, the book illuminates the ways in which ideas about race, politics, society, and crime, and forms of evidence and statistics such as rates of arrest and incarceration or the financial costs of drug policies and incarceration are advanced, interpreted, and contested. Further, the book will bring to light how people form a sense of their racial selves in debates over policy issues tied to racial inequality such as the "War on Drugs" through narratives that connect racial categories to concepts such as innocence, criminality, free will, and fairness. Debating the Drug War offers readers a variety of concepts and theoretical perspectives that they can use to make sense of these vital issues in contemporary society.
OCLC-licensed vendor bibliographic record.
Keywords: Drug control -- United States; Drug abuse -- Government policy -- United States; Crime and race -- United States; United States -- Race relations; SOCIAL SCIENCE / Sociology / General